Spring wildflowers of the Northeast : a natural history - Gracie, Carol (Princeton University Press, 2012)
Presents a detailed description of more than thirty-five wildflower species of the Northeast, describing their colors, habitats, range, pollination, history, cultural lore, medicinal uses, and literary and artistic references.